The Effect of Liquid Organic Fertilizer from Banana Pseudo-Stem on The Germination and Growth of Kabesak (Acacia leucophloea) and Angsana (Pterocarpus indicus) Seedlings - Arnold Ch Hendrik; Hartini R.L Solle; Nelci A Taek (Jurnal GALAM, 2022)
Kabesak (Acacia leucophloea) and angsana (Pterocarpus Indicus) are native plant species of Timor Island, which can be used for various purposes such as wood for construction and furniture. Efforts to cultivate these seeds need to be understood, especially by trying to use the technique of soaking seeds and watering using liquid organic fertilizer (POC) banana pseudo-stem. This study aims to determine the effect of POC banana pseudo-stem on the germination and growth of kabesak and angsana seedlings. This research is an experimentalresearch, with a completely randomized design method. There are 4 treatments of POC banana pseudo-stem concentration (25%, 50%, 75%, and 100%) and control (POC 0%). Observations of this study were carried out on germination, seedling height and number of leaves of kabesak and angsana seedlings. Data were analyzed using analysis of variance (Anova) and continued with Duncan Multiple Range Test (DMRT). The result showed that applying POC banana pseudo-stem affected germination and seedling height of kabesak, as well as germination, seedling height and the number of leaves of angsana. The growth parameter that was not affected by organic fertilizer watering was the number of leaves on the kabesak seedling. Treatment with 100% banana pseudo-stem fermented concentration was the most optimal in increasing germination, seedling height, and number of leaves of kabesak and angsana seedlings.Keywords: germination, liquid organic fertilizer, number of leaves, seedling height